2017
DOI: 10.3141/2655-10
|View full text |Cite
|
Sign up to set email alerts
|

Use of Time Domain Reflectometry to Estimate Moisture and Density of Unbound Road Materials: Laboratory Calibration and Field Investigation

Abstract: Soil moisture content and dry density of unbound granular pavement materials are important properties for compaction control that influence pavement performance under cyclic loading. Under these loading conditions, increasing moisture content can accelerate significant changes in density. Time domain reflectometry (TDR) is a method for measuring the moisture content and density of soils with rod probe sensors. This paper introduces new calibration functions for TDR measurements using these rod probe sensors em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Previous studies showed the potential of measuring both w and d with TDR (Siddiqui and Drnevich 1995;Lin et al 2000;Siddiqui et al 2000;Yu and Drnevich 2004;Drnevich et al 2005;Thring et al 2014;Jung et al 2013aJung et al , 2013bCurioni et al 2018), but these methods have not been tested in field monitoring applications. Recently, Bhuyan et al (2017) reported an interesting application of the TDR method for monitoring the condition of granular pavement materials. The aim of this paper is to demonstrate the potential use of TDR for soil condition monitoring from the measurement of w and d in a field case study.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed the potential of measuring both w and d with TDR (Siddiqui and Drnevich 1995;Lin et al 2000;Siddiqui et al 2000;Yu and Drnevich 2004;Drnevich et al 2005;Thring et al 2014;Jung et al 2013aJung et al , 2013bCurioni et al 2018), but these methods have not been tested in field monitoring applications. Recently, Bhuyan et al (2017) reported an interesting application of the TDR method for monitoring the condition of granular pavement materials. The aim of this paper is to demonstrate the potential use of TDR for soil condition monitoring from the measurement of w and d in a field case study.…”
Section: Introductionmentioning
confidence: 99%
“…For materials with an increase in moisture content, the dielectric permittivity will increase and result in a larger travel time of the pulse propagating along the conducting probes. The use of wave propagation along a three-rod probe has been used for estimating moisture content, metal, or salts in agri-food materials [98] or moisture content and density in unbound road materials [99] from electrical permittivity measurements. Inductive sensors are based on generating and detecting magnetic flux by using inductive coils.…”
Section: Electric and Magnetic Sensorsmentioning
confidence: 99%
“…Reflection and refraction occur when the electromagnetic wave meets the boundary between two kinds of media in the process of propagation. e propagation velocity of the electromagnetic wave in different media is related to the dielectric constant, as shown in equation ( 2) [28]. In general, the permeability of a nonmagnetic material (μ) is nearly the same as that of a vacuum (μ 0 ).…”
Section: Time-domain Reflectometry and Its Principlementioning
confidence: 99%